Crystal packing and theoretical analysis of halogen‐ and hydrogen‐bonded hydrazones from pharmaceuticals. Evidence of type I and II halogen bonds in extended chains of dichloromethane. Issue 6 (21st November 2018) - Berger, Gilles; Soubhye, Jalal; Wintjens, René; Robeyns, Koen; Meyer, Franck
Abstract : Supramolecular assemblies of halogenated and hydroxyl hydrazones derived from pharmaceuticals are governed by I…N and I…π halogen bonds or O—H…N hydrogen bonds. An unexpected linear arrangement of clathrated dichloromethane molecules bound through type I and II halogen bonds is observed. Theoretical calculations support the crystallographic study. Abstract : The supramolecular assembly of halogenated and hydroxyl hydrazones derived from two well known pharmaceuticals, isoniazid (Is X, where X = I, Br, OH) and hydralazine (Hy X, where X = I, Br, OH), was studied by X‐ray crystallography and theoretical methods. Crystal packing of IsI and HyI shows weak I…N and I…π halogen bonds, whereas the hydrogen bonds are dominant in the brominated scaffolds IsBr and HyBr. Although the calculated I…N interaction strength appears almost three times weaker than the O—H…N contacts in the isoniazid‐based hydrazones, the higher directionality of the halogen bonds induces a linear and planar architecture of self‐complementary tectons, observed only with the help of a bridging water molecule in the case of IsOH. Finally, the X‐ray structure of HyOH is characterized by an unexpected linear arrangement of clathrated dichloromethane molecules bound through type I and II halogen bonds. This rare phenomenon, observed in less than ten structures, was studied by coupled cluster‐based energy decomposition.